The Mediational Role of Cognitive Emotion Regulation Strategies in the Relationship of Ego-strength and Adjustment to Infertility in Women. - Negar Teimourpour; Mohammad Ali Besharat; Abbas Rahiminezhad; Batool Hossein Rashidi; Masoud Gholamali Lavasani (Tehran University of Medical Sciences, 2015)
Objective:Infertility is considered as an intense and prolonged stressful experience. Despite of high prevalence of infertility and its emotional burden for couples and especially for women, Materials and methods:the knowledge regarding psychological factors influencing adjustment to it is limited. The aim of the present study was to investigate the mediational role of cognitive emotion regulation strategies in the relationship of ego-strength and adjustment to infertility in women.A total number of 275 women with primary infertility referring to Valie-asr Reproductive Health Research Center (Tehran Imam Khomeini Hospital) participated in the present study. Data was collected via demographic information questionnaire, Ego-Strength Scale (ESS), Cognitive Emotion Regulation Questionnaire (CERQ) and Adjustment to Illness Scale (AIS). Data were analysed using Pearson correlation and path analysis methods Using SPSS (18) and LISREL (8.5) software. Results: Results indicated there are significant positive correlation between ego-strength and adjustment to infertility (r = 0.44, p < 0.01). Also Adjustment has significant positive correlation withadaptive emotion regulation strategies (r = 0.38, p < 0.01) and significant negative correlation with non-adaptive emotion regulation strategies (r = -0.43, p < 0.01). RESULTS of path analysis indicated emotion regulation strategies mediate the relationship of ego-strength and adjustment. Conclusion: These results can be helpful in making preventive policies, identifying high risk patients and planning psychological interventions.